Penggunaan Media Audio Visual untuk Edukasi Postur Kerja Pekerja Mebel di Desa Mireng Klaten - Imron Santoso, Faturohit Rois; Kusumaningrum, Tanjung Anitasari Indah (Jurnal SOLMA, 2025)
Background: Mireng Village is one of the villages in Klaten Regency which is a center for the furniture industry. Based on a preliminary survey conducted by the author, many furniture workers in Mireng Village experience complaints related to low back pain because the workers do not know the ergonomic work position. So this community service aims to increase the knowledge of furniture workers about good work posture and how to reduce the risk of low back pain in furniture workers in Mireng Village, Klaten. Method: Increasing knowledge by educating furniture workers using audio-visual media and carried out on August 16, 2024 with a total of 30 respondents. Results: There was an increase in the average knowledge of furniture workers before and after education using audio-visual media. Conclusion: The knowledge of furniture workers increased in the aspects of knowledge of poor work posture, the impact of work posture, and how to reduce the risk of low back pain. Suggestion: Health services can also provide health promotion media regarding occupational diseases, especially in the informal sector.